Engineer Richard Fiedler and his Flamethrower Epic in Russia on the Eve of the First World War - M. V. Supotnitskiy (Вестник войск РХБ защиты)
The appearance of flamethrowers as weapons is an example of the sagacity of lone individuals in the development of military equipment. Prior to World War I the German engineer Richard Fiedler invented the workable specimens of portable backpack (light) flamethrowers, trench (heavy) flamethrower, automatic igniters to flamethrowers, telescopic automatic flamethrower and other inventions, related to flamethrowing technology. Fiedler managed to reach the gunreach of jet flamethrowers to the distances that are difficult to cover even today, and also to substantiate the tactical methods of their application. Fiedler's flamethrowers were successfully tested in Russia and in Germany in 1909–1910. Using the financial interest of Fiedler, the specialists of the Chief Engineering Directorate of the Russian Military Ministry reached an agreement with him for the purchase of the latest model of the backpack flamethrower, compositions of fire mixtures for various purposes, and certain details of flamethrowers, which he kept secret as his «knowhow». However, this line was closed in Russia in 1911 by the Military Minister V.A. Sukhomlinov and his assistant A.A. Polivanov on formal grounds. Fiedler's inventions were not scrutinized by the military establishment of Great Britain and France at all. The opportunity to acquire a new type of weapons was missed for Russia and Entente Powers from the very beginning. The main reason for the indifferent attitude towards flamethrowers in the prewar period was the false ideas about the future war as a maneuverable and quick. The patents for technical solutions beyond the scope of «general ideas» about the means of warfare were also underestimated. But later they became harbingers of the emergence of new directions for the creation of weapons. It is important to take this fact into account while choosing the most promising directions for the creation of military equipment. In Germany, after almost a decade of tests and doubts, Fiedler's flamethrowers were accepted for service and delivered to pioneer detachments in 1912. They were improved and used effectively throughout the war. The Allies were to make their own flamethrowers themselves in the course of war, hastily, mainly from German models. There is no reliable information about the inventor`s fate after 1912.